The research on the applicability of different typhoon wind fields in the simulation of typhoon waves in China’s coastal waters - Chen, Xiangyu; Ni, Yunlin; Shen, Yuan; Ying, Yue; Wang, Jinbao (Frontiers in Marine Science, 2024)
A typhoon wave model of China's coastal waters was built using MIKE21 SW. By evaluating six distinct combinations of the radial air pressure distribution coefficient B and the radius of the maximum wind speed (Rmax) in the Holland wind field (HWF) model, the optimal configuration was determined. Based on the typhoon wave model, the wind velocity and significant wave heights (SWHs) were obtained using the HWF and ERA5 reanalysis data as the input wind fields to drive the typhoon waves, respectively. The validation results showed that neither the HWF nor the ERA5 wind field (EWF) accurately reflected the real wind field and SWH. A hybrid wind field (HBWF) was created by combining the HWF with the EWF using weighting coefficients that vary with the radius of wind speed, thereby compensating for the shortcomings of the two wind fields. To verify the universality of the HBWF in China's coastal waters, 14 typhoons affecting China's coastal waters were selected for numerical simulation of typhoon waves, and the error statistics were analyzed. The results indicated that the HWF accurately replicated the wind speeds near the typhoon center, with the mean relative errors of the maximum wind speed (Wmax) ranging from 8.49% to 11.82%. However, the mean relative errors for wind speeds below 10 m/s were relatively large, ranging from 25.46% to 44.29%. On the other hand, the EWF underestimated the wind speeds near the typhoon center, resulting in mean relative errors for Wmax that ranged from 17.64% to 29.37%. However, the mean relative errors for wind speeds below 10 m/s were lower than those of HWF, ranging from 18.36% to 32.00%. After simulating 14 typhoons, the mean relative errors of the significant wave heights (SWH) generated by the HWF, EWF, and HBWF were 32.48%, 27.94%, and 25.29%, respectively. The mean root mean square error (RMSE) values were 0.46 m, 0.42 m, and 0.39 m, respectively. Similarly, the consistency indices were 0.94, 0.95, and 0.96, respectively. The results show that the HBWF proposed in this study is applicable to China's coastal waters and can improve the simulation accuracy of typhoon waves.